Endoscopic ultrasound guided transbronchial fine needle aspiration: a French Department of Pathology's 4-year experience. Issue 12 (30th September 2011) - Delattre, Claire; Fournier, Clément; Bouchindhomme, Brigitte; Renaud, Florence; Escande, Fabienne; Ramon, Philippe; Copin, Marie-Christine
Abstract : Background: Endobronchial ultrasound (EBUS) guided transbronchial needle aspiration (TBNA) is an accurate outpatient procedure used to explore mediastinal lymph nodes for lung cancer staging and unexplained mediastinal masses. Aims and methods: A retrospective study was conducted over four years on EBUS-TBNA sampled lymph nodes investigated for the staging of lung cancer or unexplained mediastinal lymphadenopathies, first using the conventional method (CM) and then a liquid based cytology (LBC). Results: Of the 628 specimens (355 patients) collected, the overall rate of adequacy was 88% and the diagnosis of malignancy was achieved in 43% of cases. The inadequate rate was 6% with LBC and 21% with CM. A paraffin cytoblock was available in 80% with LBC and 62% with CM. Of the 628 aspirates, 270 (43%) were categorised as negative for malignancy including 26 cases consistent with sarcoidosis, 272 (43%) as malignant, 9 (1.4%) as suspicious for non-small-cell carcinoma and 77 as inadequate samples (12%). Of the 272 cases diagnosed as malignant, 87 (32%) were classified as non-small-cell carcinoma, 106 (39%) as adenocarcinoma, 48 (18%) as squamous cell carcinoma and 20 (7%) as small cell carcinoma. Five lymphomas, four metastatic melanomas and two carcinoids were also diagnosed. Conclusions: EBUS-TBNA is a reliable method for the staging of lung cancer and for unexplained mediastinal mass exploration. The LBC has a lower rate of inadequate samples, a better yield of cytoblock for immunohistochemistry and a dramatically reduced time requirement for interpretation as compared to CM.